2021
DOI: 10.5090/jcs.20.149
|View full text |Cite
|
Sign up to set email alerts
|

Hemopneumothorax as an Unusual and Delayed Complication of Coronavirus Disease 2019 Pneumonia: A Case Report

Abstract: The increasing number of studies published on coronavirus disease 2019 (COVID-19) pneumonia has improved our knowledge of the disease itself and its complications. Despite a considerable number of publications on COVID-19 pneumonia-associated pneumothorax, no article on spontaneous hemopneumothorax has been found in the English-language literature. According to published case reports, pneumothorax generally occurs in hospitalized patients during treatment, whereas cases that arise in the late period after disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…Ozdemir et al reported that the effects of age and diseases associated with pneumothorax in their study on intubated patients with COVID-19 were not significant (18). However, in our case and the case reported by Sayan et al, there were no underlying diseases prior to COVID-19 (12). A study in the United States also showed that most individuals with hemopneumothorax due to COVID-19 infection had a mean age of 60 years, and most of the samples had an underlying disease (19).…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Ozdemir et al reported that the effects of age and diseases associated with pneumothorax in their study on intubated patients with COVID-19 were not significant (18). However, in our case and the case reported by Sayan et al, there were no underlying diseases prior to COVID-19 (12). A study in the United States also showed that most individuals with hemopneumothorax due to COVID-19 infection had a mean age of 60 years, and most of the samples had an underlying disease (19).…”
Section: Discussioncontrasting
confidence: 58%
“…Chen et al reported that about 1% of individuals with COVID-19 developed a pneumothorax (8). A case report showed that most patients suffering from hemopneumothorax were elderly and had an underlying disease (12). Ozdemir et al reported that the effects of age and diseases associated with pneumothorax in their study on intubated patients with COVID-19 were not significant (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary spontaneous pneumothorax (SP) caused by COVID‐19 has been recorded on several occasions at the time of diagnosis or during therapy. However, late‐onset spontaneous pneumothorax in individuals who recovered from COVID‐19 is rare 5 . Here, we present a case of an adult male with previously diagnosed COVID‐19 who developed spontaneous pneumothorax after seventeen days of recovery.…”
Section: Introductionmentioning
confidence: 94%
“…However, late‐onset spontaneous pneumothorax in individuals who recovered from COVID‐19 is rare. 5 Here, we present a case of an adult male with previously diagnosed COVID‐19 who developed spontaneous pneumothorax after seventeen days of recovery.…”
Section: Introductionmentioning
confidence: 99%